Electrochemical Removal of Different Phases from Laser Solid Formed Inconel 718. Issue 7 (1st January 2017) - Guo, Pengfei; Lin, Xin; Xu, Jianjun; Li, Jiaqiang; Liu, Jianrui; Huang, Weidong
Abstract : To overcome the difficulty on manufacturing of large high-performance Inconel 718 parts with high efficiency and precision by traditional processing methods, we propose the laser/electrochemical hybrid precision forming technology. Here, the electrochemical behavior of different phases in laser solid formed (LSFed) Inconel 718 was investigated based on the analysis of surface micromorphology, surface products and polarization tests. The results showed that Nb-rich γ phase dissolves faster than γ matrix due to its higher lattice distortion energy and more negative electrode potential. The high free energy of atoms on phase boundaries also accelerates the dissolution of Nb-rich γ phase. Further, the secondary phases surrounded by Nb-rich γ phase fall out by undermining. Compared with γ matrix, Nb-rich γ phase possesses a lower onset potential because of its negative electrode potential. Moreover, qualitative model has been assumed to illustrate the electrochemical removal behavior of phases. These results provide an insight to improve the surface quality of LSFed Inconel 718 parts during the process of electrochemical machining.